A new infrared spectroscopy sample presentation unit for measuring feeding quality of maize stover - Montes, J.M.; Mirdita, V.; Prasad, K.; Blümmel, Michael; Melchinger, A.E. (SAGE Publications, 2009)
Maize stover is used to feed farm animals and the improvement of its quality is an important breeding goal. The main objective of our study was to evaluate a new near infrared (NIR) spectroscopy sample presentation unit for measuring feed quality of maize stover. In this context, we investigated the effect of engineering factors (use of glass interface and packing pressure) on the spectral repeatability and the effect of particle sizes (8 cm, 6 cm, 4 cm, 0.5 cm) on the calibration performance. The spectral repeatability was examined by calculating spectral variation among replicated spectral measurements collected without glass interface, with glass interface, and glass interface in combination with 3 kg and 6 kg of packing pressure. The effect of particle sizes was assessed for concentrations of nitrogen (N), neutral detergent fibre (NDF), ash and in vitro fermentability (G24), by examining calibration models. The spectral repeatability increased with the use of glass interface and packing pressure and calibration performance improved with a reduction in particle size. The study indicated that the new NIR sample presentation unit has a potential for preliminary screenings of maize genotypes for NDF and G24 in the stover of particular breeding programmes.